2017
DOI: 10.1002/2016ja023634
|View full text |Cite
|
Sign up to set email alerts
|

Roles of whistler mode waves and magnetosonic waves in changing the outer radiation belt and the slot region

Abstract: Using the Van Allen Probe long‐term (2013–2015) observations and quasi‐linear simulations of wave‐particle interactions, we examine the combined or competing effects of whistler mode waves (chorus or hiss) and magnetosonic (MS) waves on energetic (<0.5 MeV) and relativistic (>0.5 MeV) electrons inside and outside the plasmasphere. Although whistler mode chorus waves and MS waves can singly or jointly accelerate electrons from the hundreds of keV energy to the MeV energy in the low‐density trough, most of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 78 publications
2
67
0
Order By: Relevance
“…As a result, the two-layer structure in the Pedersen conductivity profile also appears before the storm (Figure 2c). The prestorm two-layer feature at 60 ∘ is a result of wave-particle interactions inside the plasmapause where hiss waves are able to scatter electrons above 10 keV (Li et al, 2015), while the storm time high-energy tail is originated from the chorus wave scattering outside the plasmapause. The prestorm two-layer feature at 60 ∘ is a result of wave-particle interactions inside the plasmapause where hiss waves are able to scatter electrons above 10 keV (Li et al, 2015), while the storm time high-energy tail is originated from the chorus wave scattering outside the plasmapause.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…As a result, the two-layer structure in the Pedersen conductivity profile also appears before the storm (Figure 2c). The prestorm two-layer feature at 60 ∘ is a result of wave-particle interactions inside the plasmapause where hiss waves are able to scatter electrons above 10 keV (Li et al, 2015), while the storm time high-energy tail is originated from the chorus wave scattering outside the plasmapause. The prestorm two-layer feature at 60 ∘ is a result of wave-particle interactions inside the plasmapause where hiss waves are able to scatter electrons above 10 keV (Li et al, 2015), while the storm time high-energy tail is originated from the chorus wave scattering outside the plasmapause.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To evaluate the effect of the LH MS waves on the radiation belt electrons, we used a widely used Gaussian model (e.g., Horne et al, ; Li, Yu, et al, ; Maldonado et al, ) to fit the frequency spectrum distribution of the observed waves, given as follows: g1()ω={A1exp][ωωnormalm/δω20.5emωlc<ω<ωuc;010.25emotherwise,1em A1=1δω2normalπ1/2erfωmωlcδω+erfωucωmδω1, …”
Section: Effect Of Low‐harmonic Ms Waves On the Radiation Belt Electronsmentioning
confidence: 99%
“…Recently, wave‐particle interaction is put forward to explain the formation of butterfly distribution far away from the magnetopause. MS waves are believed to be a candidate mechanism responsible for the butterfly formation through Landau resonance (Horne et al, ; Li, Yu, et al, ; Xiao et al, ; Yang et al, ), transit time scattering (Bortnik & Thorne, ; Li et al, ; J. Li, Ni, et al, ; Ni et al, , ), and bounce resonance (Chen et al, ; Li & Tao, ; Maldonado et al, ; Shprits, ; Tao & Li, ). Landau resonance occurs when the parallel phase velocity ( ω / k ∥ ) of waves equals to the electron velocity parallel to background magnetic field ( v ∥ ; Artemyev et al, ) and the minimum resonant energy can be obtained according to the study of Horne et al ().…”
Section: Introductionmentioning
confidence: 99%
“…While the numerical representation of the geospace system is being greatly improved, better characterization of physics in the near‐Earth environment has also been consistently obtained. For example, the wave dynamics and their impact on plasma dynamics have been analyzed in great detail (e.g., Blum et al, , , ; Fu et al, ; Kim et al, ; W. Li et al, ; J. Li, Ni, et al, ; L. Y. Li, Yu, et al, , ; L. Li, Zhou, et al, ; Ma, Li, et al, ; Murphy et al, ; Shi et al, ; Shprits, Drozdov, et al, ; Turner et al, , ; Usanova et al, ; Wang, Pan, et al, ; Wang, Zhai, et al, ; J. Yu et al ; J.‐C. Zhang et al, ; X.‐J.…”
Section: Advancements On Imcepi Topics During the Imcepi Years (2014–mentioning
confidence: 99%